The utilization of YAP Scintillation Detector for Soft Gamma Radiation Measurement in Backscatter Thickness Gauge - M. Zainuddin; Yustina Tri Handayani; Sugino Sugino; Hiroshi Tominaga (Widyanuklida, 2006)
ABSTRACT Interesting properties of a YAP(Ce) scintillator make it an alternative solution for low energy gamma measurement in high counting rates that previously employed GM counter tubes and/or Nal(Tl) scintillators. Some characteristics of the YAP(Ce) crystal combined with a photomultiplier tube have been successfully demonstrated in a backscatter mode of thickness gauging with 241Am gamma-source.